Strain evolution of SiGe-on-insulator obtained by the Ge-condensation technique - Victor Boureau; Shay Reboh; Daniel Benoit; Martin Hÿtch; Alain Claverie (APL Materials, 2019)
Compressively strained SiGe-On-Insulator (SGOI) made by the Ge-condensation technique is used as a performance booster for ultrathin fully depleted silicon-on-insulator transistor technology. Here, we report on the evolution of the compressive strain in the SiGe film along the formation of local SGOI. For this, experimental maps of lattice strain with nanometer spatial resolution have been obtained by dark-field electron holography and compared to results from numerical models describing the mechanics of the structures. In particular, we report on unexpected strain evolutions when the top semiconductor layer is patterned to fabricate the shallow trench isolations that separate the Si nMOS from the SiGe pMOS areas. Dramatic and long-range relaxation of the compressive SiGe layers occurs, while no extended defects are formed in the crystal. The phenomenon involves relative horizontal displacements between the SiGe layer and the underlying Buried Oxide (BOX). We suggest that the Ge-enrichment of the layer close to this interface by the Ge-condensation technique modifies the SiGe/BOX interface and that strain relaxation results from the propagation of some interfacial defects from the edge to the center of the structure, driven by the shear stress at the interface.